2022
DOI: 10.37616/2212-5043.1286
|View full text |Cite
|
Sign up to set email alerts
|

Isolated reoperative tricuspid valve surgery: Outcomes and risk assessment

Abstract: Objective To describe patient characteristics and post-operative outcomes, including early and late mortality, defined by death within 30 days and after 30 days post-surgery, respectively, as well as 20-year survival after isolated reoperative tricuspid surgery. Methods We retrospectively analyzed 169 patients who underwent isolated reoperative tricuspid valve surgery at our institution (between 1997 and 2000) and describe post-surgical outcomes including intraoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“… 10 , 11 Other studies have reported in-hospital mortality rates within a varying range of 10 to 13%. 12 , 13 , 14 The individualized perioperative care provided by a single surgeon in our Mini-TVS experience may have contributed to the positive surgical outcomes in this cohort. Furthermore, our previous ITV national outcomes study showed no difference in in-hospital mortality between TVR and TVre.…”
Section: Discussionmentioning
confidence: 97%
“… 10 , 11 Other studies have reported in-hospital mortality rates within a varying range of 10 to 13%. 12 , 13 , 14 The individualized perioperative care provided by a single surgeon in our Mini-TVS experience may have contributed to the positive surgical outcomes in this cohort. Furthermore, our previous ITV national outcomes study showed no difference in in-hospital mortality between TVR and TVre.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, TVIR replacement has been introduced as an appealing alternative for TR after failed surgical annuloplasty, with initial reports showing successful clinical outcomes. 2 , 3 , 4 , 5 , 6 While comparing with tricuspid valve‐in‐valve replacement, TVIR in general encounters the increasing complexity in pathological structure and has higher risk of developing complications: (i) In contrast to the geometry of the left‐sided valve annulus, which is circular, the geometric dimensions of the dilated TA after surgical annuloplasty repair are larger, oval, and non‐planar. 2 (ii) It is difficult to maintain the prosthesis coaxially with the TA after surgical annuloplasty repair in cases with severe TR and a giant right atrium.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent tricuspid regurgitation (TR) is observed in over 10% of patients in the short‐term follow‐up after prior surgical annuloplasty procedures, leading to increased mortality rates and unfavourable clinical outcomes 1 . Similarly, a surgical reoperation is a less effective way to deal with recurrent TR because of its historically high risk and high postoperative mortality 2 . For these patients, transcatheter tricuspid valve‐in‐ring (TVIR) replacement has emerged as a viable alternative to high‐risk surgical reoperation for failed annuloplasty rings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Managing such patients presents challenges, and the mortality associated with a repeat TV surgery remains high. This underscores the critical importance of evaluating the function of prosthetics TV 1,2 Echocardiography plays a crucial role in evaluating tricuspid prostheses. Given the anterior position of the TV, transthoracic echocardiography (TTE) generally offers satisfactory assessment of prosthetic TV 3 .…”
Section: Introductionmentioning
confidence: 99%